factorise it into brackets. The equation is actually x2-6x+0. So into brackets it will be (x-6)(x+0) = 0. From here, to solve the equation, make either of the brackets = 0 by substituting a value for x. In this instance x = 0 or 6.
Chat with our AI personalities
Guesswork!
Presumably there's a minus sign missing, in which case x = 6 as 62 = 6 x 6
If: x2-6x-13 = 14 Then: x2-6x-27 = 0 And: (x+3)(x-9) = 0 So: x = -3 or x = 9
x2+6x+9 = x+3 x2+6x-x+9-3 = 0 x2+5x+6 = 0 Solve by factoring or with the help of the quadratic equation formula: (x+3)(x+2) = 0 Therefore: x = -3 or x = -2
x2+6x-40 = 0 (x+10)(x-4) = 0 x = 4 or x = -10
x2 + 6x - 110 = 0 ∴ x2 + 6x = 110 ∴ x2 + 6x + 36 = 146 ∴ (x + 6)2 = 146 ∴ x + 6 = ±1461/2 ∴ x = -6 ±1461/2 ∴ x ≈ 6.083, 18.083
x2 +6x = 27 x2 + 6x - 27 = 0 x2 + 9x - 3x - 27 = 0 x(x + 9) - 3(x + 9) =0 (x - 3)(x + 9) = 0 So x can equal 3 or -9.